Hypertension and the J-curve. How low should you go? - Onrot, J. (College of Family Physicians of Canada, 1993)
Recent analyses of treated blood pressure versus events suggest that drug treatment might result in an increase in coronary events or mortality at treated diastolic pressures below 80 mm Hg (the "J-curve"). However, this contention is highly controversial. Both sides of the argument are examined and a balanced approach for target blood pressure goals on treatment is outlined.